Peripheral blood CD56bright NK cells respond to stem cell factor and adhere to its membrane‐bound form after upregulation of c‐kit. Issue 2 (20th November 2013) - Pradier, Amandine; Tabone‐Eglinger, Severine; Huber, Vincent; Bosshard, Carine; Rigal, Emmanuel; Wehrle‐Haller, Bernhard; Roosnek, Eddy
<x xml:space="preserve">Abstract</x> CD56bright NK cells express receptors for IL‐2, IL‐7, IL‐15, and SCF. We found that human peripheral blood CD56bright NK cells responded to IL‐2, IL‐7, IL‐15 by phosphorylating STAT‐5, ERK, and Akt but did not respond to SCF. However, CD56bright NK cells in culture upregulated c‐kit transcription three to fourfold, which led to a steady increase in c‐kit and a concomitant acquisition of responsiveness to SCF. After 44 h, CD56bright NK cells had upregulated c‐kit approximately 20‐fold and phosphorylated ERK and Akt in response to SCF concentrations well below levels present in plasma. CD56bright NK cells cultured in IL‐15 maintained c‐kit transcription/expression at ex vivo levels and did not become responsive to SCF. Furthermore, SCF‐responsive, CD56brightc‐kithigh NK cells swiftly downregulated c‐kit and stopped responding to SCF after IL‐15 stimulation. However, commitment of CD56bright NK cells to a c‐kit‐negative, SCF‐unresponsive state did not occur, as after 5 days of culture, withdrawal of IL‐15 restored c‐kit to maximal levels and reestablished SCF‐responsiveness. CD56bright NK cells that had upregulated c‐kit firmly adhered to COS cells transfected with the membrane form of SCF. Furthermore, SCF signaling significantly increased the capacity of CD56bright NK cells to degranulate. Collectively, our data suggest that c‐kit on human CD56bright NK cells is a functional receptor that is downregulated in peripheral blood, possibly to render CD56bright NK cells unresponsive to the SCF therein.